Evaluasi Kritis Penggunaan Membangun Jemaat Dari Perspektif Teologi Kontekstual - Oktoviandy, Oktoviandy (Sekolah Tinggi Agama Kristen Negeri Toraja, 2018)
Using a qualitative approach we researched and then evaluated the use model of the book Building a Church in the Toraja Church in the South Sangalla Klasis by using a perspective on contextual theology. In this study we found 2 (two) models of using the Church Building book used by the servants there, namely the translation model and the post-translation model. We evaluate these two models as a model of use that is not sufficient to be able to bring the church to the celebration of God's great presence and work that surrounds all. We evaluate Both of these models is still very narrow in providing space for the development of theology and/ or preaching that is truly contextual. AbstrakDengan menggunakan pendekatan kualitatif kami meneliti untuk kemudian mengevaluasi model penggunaan buku Membangun Jemaat di Gereja Toraja se-Klasis Sangalla’ Selatan dengan menggunakan perspektif teologi kontekstual. Dalam penelitian ini kami menemukan 2 (dua) model penggunaan buku Membangun Jemaat yang digunakan oleh para pelayan di sana, yakni model terjemahan dan model post-terjemahan. Kedua model tersebut kami nilai sebagai model penggunaan yang belum memadai untuk bisa membawa jemaat (gereja) kepada perayaan akan kemahahadiran dan karya Allah yang besar dan yang melingkupi semua. Kedua model itu, kami nilai masih sangat sempit dalam memberi ruang bagi pengembangan teologi dan/atau khotbah yang sungguh-sungguh kontekstual.